Single group multisite safety trial of sibling cord blood cell infusion to children with cerebral palsy: study protocol and rationale. Issue 3 (8th March 2020) - Crompton, Kylie; Novak, Iona; Fahey, Michael; Badawi, Nadia; Wallace, Euan; Lee, Katherine; Mechinaud-Heloury, Francoise; Colditz, Paul B; Elwood, Ngaire; Edwards, Priya; Reddihough, Dinah
Abstract : Introduction: Cerebral palsy (CP) is the most common physical disability of childhood but has no cure. Stem cells have the potential to improve brain injury and are proposed as a therapy for CP. However, many questions remain unanswered about the most appropriate cell type, timing of infusions, dose required and associated risks. Therefore, human safety and efficacy trials are necessary to progress knowledge in the field. Methods and analysis: This is a single group study with sample size n=12 to investigate safety of single-dose intravenous 12/12 human leucocyte antigen-matched sibling cord blood cell infusion to children with CP aged 1–16 years without immune suppression. The study is similar to a 3+3 design, where the first two groups of participants have severe CP, and the final six participants include children with all motor severities. Children will be monitored for adverse events and the duration that donor cells are detected. Assessments at baseline, 3 and 12 months will investigate safety and preliminary evidence of change in gross motor, fine motor, cognitive and quality of life outcomes. Ethics and dissemination: Full approval was obtained from The Royal Children's Hospital Human Research Ethics Committee, and a clinical trial notification was accepted by Australia's Therapeutic Goods Administration. Participant guardian informed consent will be obtained before any study procedures. The main results of this study will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12616000403437, NCT03087110 .